2008
DOI: 10.1108/09615530810879747
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection in a horizontal cylindrical annulus using porous fins

Abstract: PurposeThe aim is to study the effects of fin conductivity ratio, Darcy number, and Rayleigh number on the average Nusselt number for fins made of porous material when attached to the inner cylinder of the annulus between two concentric cylinders. The paper also aims to compare the results with those obtained using solid fins over a range of Rayleigh numbers.Design/methodology/approachThe Darcy‐Brinkman equations were used to model the fluid flow inside the porous media and the Boussinesq approximation was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 13 publications
(31 reference statements)
1
52
0
Order By: Relevance
“…Abu-Hijleh [12] analysed the effects of using permeable fins on the forced convection heat transfer from a horizontal cylinder. The results obtained were similar to results obtained as per Kiwan and Zeitoun [10] in terms of the permeable fins providing much higher heat transfer rates. To study radial fins, a combination of the Taylor transformation and finite difference approximation was implemented by Yu and Chen [13,14].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Abu-Hijleh [12] analysed the effects of using permeable fins on the forced convection heat transfer from a horizontal cylinder. The results obtained were similar to results obtained as per Kiwan and Zeitoun [10] in terms of the permeable fins providing much higher heat transfer rates. To study radial fins, a combination of the Taylor transformation and finite difference approximation was implemented by Yu and Chen [13,14].…”
Section: Introductionsupporting
confidence: 90%
“…He further discovered that, by choosing a precise value for the thermal conductivity ratio and the fin length to thickness ratio, the performance of the porous fin exceeded the performance of the solid fin. A study was conducted by Kiwan and Zeitoun [10] to test the performance of rectangular porous fins mounted around the inner cylinder of a cylindrical annulus by performing a finite volume type numerical study. It was concluded that, in comparison to solid fins, porous fins provided higher transfer rates for similar configurations and that the heat transfer rate from the cylinder equipped with porous fins decreased as the fin inclination increased.…”
Section: Introductionmentioning
confidence: 99%
“…In order to verify the numerical code, the results of the present code are tested and compared with the results obtained by Kiwan and Zeitoun (2007). The mixed convection in rectangular cavity with moving isothermal sidewalls and constant flux heat source on the bottom is solved numerically.…”
Section: Porous Layermentioning
confidence: 99%
“…They presented the values of the critical thermal conductivity ratio for different flow cases. The effect of attaching two porous fins on the inner cylinder in the annuli between two horizontal concentric cylinders was studied by Kiwan and Zeitoun (2007). They found that the heat transfer using porous fins is enhanced when compared with that of solid fins.…”
Section: Introductionmentioning
confidence: 99%
“…The fin is porous to allow the flow of infiltrating through it. Extensive research has been done in this area and many references are available, especially for heat transfer in porous fins [1][2][3][4][5]. Described below are a few papers relevant to the study described herein.…”
Section: Introductionmentioning
confidence: 99%